Mapping the Marine Environment Through a Cross-Cultural Collaboration - Davies, Harriet N.; Gould, Jackie; Hovey, Renae K.; Radford, Ben; Kendrick, Gary A.; , The Anindilyakwa Land and Sea Rangers; , Anindilyakwa Traditional Owners (Frontiers in Marine Science, 2020)
There is a growing emphasis on formally recognizing the connection to the marine environment of Indigenous peoples and the traditional ecological knowledge (TEK) these strong connections cultivate. The potential for TEK to significantly enrich the scientific comprehension of the marine environment, whilst also celebrating the rich bio-cultural knowledge in its own right, is indisputable. Here, we present a scientifically robust and culturally appropriate participatory mapping methodology for the marine environment which can effectively achieve genuine cross-cultural ecological knowledge transfer between scientists and Indigenous Peoples. Through a case study working with the Anindilyakwa people of the Groote Eylandt Archipelago, we mapped the TEK of benthic habitats off Australia’s poorly surveyed northern coast. Representatives from 14 Anindilyakwa clan groups participated in the marine mapping (n=53), resulting in 22 individual maps. Eleven broad-scale habitat classifications, predominately in the intertidal and nearshore marine environment, were described in both Anindilyakwa and English. The information gathered was then used to develop benthic habitat maps covering a combined area of ~1800km2 and was assessed for accuracy against in-situ observations. We found that despite the difficulties in working across two different world views, through the application of this carefully refined methodology, scientists can effectively document the rich TEK of the marine environment in a manner suitable for conservation and management planning while also supporting the prioritization of Indigenous values within the decision-making process.